Chiral 1,4-Hydroxyarylalcohols (HAROLs) and 1,4-Aminoalkylphenols (AAPs) as Organocatalysts for Asymmetric Hetero Diels-Alder Reaction - (:unkn) unknown (My University, 2019)
In this study, two chiral 2-(2-hydroxyaryl) alcohols (HAROLs; 1,4-diols) and a 1,4-aminoalkylphenol (AAP) were examined as hydrogen-bond donor (HBD) organocatalysts in the asymmetric hetero Diels-Alder (HDA) reaction of aldehydes with Rawal’s diene. Catalytic amount (10 mol%) of the both scaffolds (HAROL and AAP) have been found to effect the HDA reaction in a quite efficient manner. Among them, a HAROL molecule based on indan backbone was turned out to be the best in terms of catalytic activity and enantioselectivity. On the other hand, AAP tested seemed to act as a bifunctional organocatalyst, i.e. as both a Lewis base and HBD organocatalyst. Experimental results underpins that a careful tuning of HAROL structure might lead to the development of more general HBD organocatalysts.

Bu çalışmada, iki tane kiral 2-(2-hidroksiaril) alkol (HAROL, 1,4-diol) ve bir 1,4-aminoalkilfenol (AAP), aldehitlerin Rawal dieni ile asimetrik hetero Diels-Alder (HDA) reaksiyonunda hidrojen-bağı donörü (HBD) organokatalizörleri olarak incelenmiştir. Her iki yapının (HAROL ve AAP) katalitik miktarının (%10) HDA reaksiyonunu oldukça verimli bir şekilde gerçekleştirdiği bulunmuştur. Bunlar arasında, indan iskeleti bazlı bir HAROL molekülünün, katalitik aktivite ve enantioseçicilik bakımından en iyisi olduğu ortaya çıkmıştır. Öte yandan, test edilen AAP bifonksiyonlu bir organokatalizör olarak, diğer bir deyişle bir Lewis bazı ve HBD organokatalizörü gibi davranıyor görünmektedir. Deneysel sonuçlar HAROL yapısının dikkatli bir şekilde ayarlanmasının, daha genel HBD organokatalizörlerinin geliştirilmesine yol açabileceğini desteklemektedir.
Asimetrik Hetero Diels-Alder Reaksiyonu için Organaokatalizör Olarak Kiral 1,4-Hidroksiarilalkoller (HAROL) ve 1,4-Aminoalkilfenoller (AAP)